Ab Initio Potential Energy Surfaces for Both the Ground (X̃1A′) and Excited (A∼1A′′) Electronic States of HSiBr and the Absorption and Emission Spectra of HSiBr/DSiBr. (13th October 2011) - Li, Anyang; Lin, Sen; Xie, Daiqian
Abstract : Ab initio potential energy surfaces for the ground (X ̃ 1 A ′ ) and excited (A ˜ A ′′ 1 ) electronic states of HSiBr were obtained by using the single and double excitation coupled-cluster theory with a noniterative perturbation treatment of triple excitations and the multireference configuration interaction with Davidson correction, respectively, employing an augmented correlation-consistent polarized valence quadruple zeta basis set. The calculated vibrational energy levels of HSiBr and DSiBr of the ground and excited electronic states are in excellent agreement with the available experimental band origins. In addition, the absorption and emission spectra of HSiBr and DSiBr were calculated using an efficient single Lanczos propagation method and are in good agreement with the available experimental observations.